The Legal Standing of the Anak Dalam Tribe in Initiating Class Action Lawsuits Regarding Land Disputes - Adithiya Diar; Lestari, Amanda Dea (Faculty of Law, Universitas Pasundan, 2025)
This article examines the persistent influence of legal formalism within Indonesia’s civil justice system and its implications for the protection of Indigenous Peoples’ customary land rights, particularly through class action litigation and the doctrine of legal standing. Land disputes involving Indigenous communities reflect structural injustice, as legal recognition remains heavily dependent on administrative validation rather than historical, social, and cultural realities. Consequently, Indigenous Peoples often face significant barriers in accessing justice, despite constitutional acknowledgment of their existence and rights. Using normative legal research, this study analyzes statutory frameworks, judicial decisions, and doctrinal approaches governing class actions and legal standing in Indonesia. The findings demonstrate that existing procedural mechanisms frequently marginalize Indigenous communities by imposing rigid standing requirements and evidentiary standards that are incompatible with their collective and customary social structures. Rather than functioning as instruments of empowerment, class actions often reproduce exclusion through excessive proceduralism. The study argues that Indigenous marginalization stems not from the absence of substantive rights, but from the dominance of formalistic reasoning that prioritizes administrative legality over substantive justice. To address this imbalance, the article proposes a normative reconstruction of civil procedural law, including the establishment of a lex specialis on class actions and Indigenous legal standing, the contextual reinterpretation of standing doctrines, the integration of ecological and social justice principles, and the adoption of participatory and culturally responsive judicial approaches. These reforms are essential to ensure equitable access to justice within Indonesia’s plural legal system.